Logic Models on Health Information Technology: First Insights from a CrossDisciplinary Scoping Review...36th Medical Informatics Europe (MIE) Conference, May 25-28, 2026, Genoa, Italy - AMMENWERTH, Elske; BINDEL, Michelle; HÖRHAMMER, Iiris (Studies in Health Technology & Informatics, 2026)
Background: Health information technology (HIT) interventions are complex, yet theory-based approaches such as logic models or Theory of Change (ToC) remain rarely applied in medical informatics, although they could clarify assumptions, link activities to outcomes, and support design and evaluation. Objectives: This scoping review examined how logic models and ToC have been used in HIT research across disciplines. Methods: Following the PRISMA-ScR guidelines, databases were searched up to August 2025. Eligible studies explicitly applied logic models or ToC to HIT. Data were extracted on HIT type, purpose of using logic models, and reported benefits and challenges. Results: Sixty-nine studies met inclusion criteria, most published after 2020. A majority of studies developed logic models for patient-facing HIT such as mHealth or telehealth. Logic models were mainly used to support HIT design or evaluation and were mostly newly developed. Reported benefits of using logic models included conceptual clarity and better stakeholder communication; challenges involved resource demands and limited generalisability. Conclusions: Logic models and ToC are increasingly used for HIT but remain inconsistently applied and seldom reused. Standardised reporting and repositories could strengthen theory-informed evaluation in medical informatics.